Prognostic value of microRNA expression pattern in upper tract urothelial carcinoma. (May 2014) - Izquierdo, Laura; Ingelmo‐Torres, Mercedes; Mallofré, Carmen; Lozano, Juan José; Verhasselt‐Crinquette, Marie; Leroy, Xavier; Colin, Pierre; Comperat, Eva; Roupret, Morgan; Alcaraz, Antonio; Mengual, Lourdes
<x xml:space="preserve">Abstract</x> Objective To examine the microRNA (miRNA) expression pattern in tumour samples from patients with progressing and non‐progressing upper tract urothelial carcinoma (UTUC) in order to identify putative miRNAs that may be used as prognostic markers. Patients and Methods We conducted a multicentre, retrospective study of formalin‐fixed paraffin‐embedded tissue samples from 150 patients with UTUC who had undergone radical nephroureterectomy. Global miRNA expression patterns were analysed in 18 selected samples from patients with UTUC using TaqMan arrays. The differential expression of five key miRNAs was validated by quantitative polymerase chain reaction in an independent cohort of 132 samples from patients with UTUC. Models to predict tumour progression and cancer‐specific survival that included miRNA expression patterns were developed by Cox regression analysis. Results Twenty‐six miRNAs were found to be aberrantly expressed between samples from patients with progressing and non‐progressing UTUC and five of these were selected for subsequent studies. The regression analysis identified tumour stage and miR‐31 and miR‐149 expression as independently associated with tumour progression and tumour stage and miR‐149 expression as independently associated with cancer‐specific survival. The risk scores derived from these miRNA models were able to discriminate two groups with a highly significantly different probability of tumour progression (hazard ratio [HR] 4.78; P < 0.001) and death (HR 276; P = 0.004). Conclusions There is a differential miRNA expression pattern between patients with progressing and non‐progressing UTUC. The identification of new miRNAs associated with a high probability of tumour recurrence and cancer‐specific survival in patients with UTUC and their combination in a robust, easy‐to‐use and reliable algorithm may help tailor treatment and surveillance strategies in these patients.